The integrin repertoire drives YAP-dependent epithelial:stromal interactions during injury of the kidney glomerulus - Evelyne Huynh-Cong; Victoria Driscoll; Sandrine Ettou; Keith Keller; Amha Atakilit; Mary E. Taglienti; Saurabh Kumar; Astrid Weins; Valerie A. Schumacher; Jordan A. Kreidberg (Nature Communications)
Abstract The kidney glomerulus is a filtration barrier in which capillary loop architecture depends on epithelial-stromal interactions between podocytes and mesangial cells. Podocytes are terminally differentiated cells within the glomerulus that express YAP and TAZ. Here we test the hypotheses that YAP and TAZ are required in podocytes to maintain capillary loop architecture and that shifts in the integrin repertoire during podocyte injury affect transcriptional activity of YAP and TAZ. Loss of YAP in podocytes of adult mice renders them more sensitive to injury, whereas loss of both YAP and TAZ in podocytes rapidly compromises the filtration barrier. α3β1 and αvβ5 are two prominent integrins on murine podocytes. Podocyte injury or loss of α3β1 leads to increased abundance of αvβ5 and nuclear localization of YAP. In vitro, blockade of αvβ5 decreases nuclear YAP. Increased αv integrins are found in human kidney disease. Thus, our studies demonstrate the crucial regulatory interplay between cell adhesion and transcriptional regulation as an important determinant of human disease.